1995
DOI: 10.3109/15563659509010624
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Identification of Lead Sources in Preschool Children – The Omaha Study

Abstract: The objective was to determine, from analysis of the naturally occurring stable isotopes of lead, the relative contribution of food, handdust, housedust, soil and air lead to the absorbed (urinary) lead and the blood lead of children living in a former smelter city. A longitudinal 12 month study was conducted of 21 children, 2 - 3 years of age, living in central Omaha, balanced for race, gender and socioeconomic status. Field clean samples were collected monthly of 24 hour duplicate diet, handwipe and urine, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 3 publications
3
15
1
Order By: Relevance
“…That is, the absorption away from home, and potentially a greater argument also fails to explain the cases in rate is around 10-15% rather than 40-50%. intake of lead from dust/dirt with the which the diet shows an increase in both Our interpretations are supported by data of Australian isotopic composition compared intake and isotopic composition, such as for Angle et al (33) in which they suggested that with adult women; 2) the children are subjects 2015 (Fig. 9) …”
Section: Discussionsupporting
confidence: 75%
“…That is, the absorption away from home, and potentially a greater argument also fails to explain the cases in rate is around 10-15% rather than 40-50%. intake of lead from dust/dirt with the which the diet shows an increase in both Our interpretations are supported by data of Australian isotopic composition compared intake and isotopic composition, such as for Angle et al (33) in which they suggested that with adult women; 2) the children are subjects 2015 (Fig. 9) …”
Section: Discussionsupporting
confidence: 75%
“…Because of the operational and social difficulties associated with collecting the required number of venous blood samples from all the newborn infants, urine samples were also collected at 10, 30, 60, 90, 120, 150, and 180 days into pediatric urine collectors and transferred into precleaned polyethylene botdes. Angle et al (12) and Gulson et al (13) have shown that the isotopic compositions of urine generally conform well with those for blood with correlations of better than 0.9.…”
Section: Samplingmentioning
confidence: 96%
“…Hunt et al (77) and Adgate and colleagues (140,141) were among the first groups to attempt multiple source signature Review • Lioy et al identification and differentiation (142). In the case of Hunt et al (77) and Adgate et al (140), the analyses were done for lead present in residential carpets and other surfaces, respectively.…”
Section: Assessment Of Data Obtained From Residential Dustmentioning
confidence: 99%